Integrating outer space as a global commons with private property rights to outer space resources - Mei, Di (Frontiers in Space Technologies, 2024)
Inspired by the US government's denial that outer space is a global commons, and the heated discussion in China regarding property rights in outer space resources, this article looks at this controversial term: "global commons". It finds that this term was mostly adopted as a political, rather than legal, term. As a result of the over-emphasis on the implications of global commons on the property rights to outer space resources, states that plan to develop private space mining may avoid calling outer space a global commons. This article argues that this response may not be necessary. It then examines the real purpose of the global commons discourse by analogizing the tragedy of commons and thus puts forward the suggestion to adopt the non-exclusive use standard to govern the activities of space resource extraction by private parties. This solution will allow countries to continue to view outer space as a global commons while liberalizing private parties' activities in outer space resource development and extraction. Moreover, China's initiative of the global community of shared future possesses the potential to serve as the overarching concept to govern its future outer space activities, including space mining.